High polymorphism in Plasmodium vivax merozoite surface protein-5 (MSP5) (2006)
A key issue relating to developing multi-component anti-malarial vaccines, lies in studying Plasmodium vivax surface proteins' genetic variation. The present work was aimed at amplifying, cloning and sequencing the gene encoding P. vivax merozoite surface protein 5 (PvMSP5) in samples obtained from infected patients from Colombian areas having varying malaria transmission rates.Nucleotide sequence data reported in this paper are available in the GenBank, EMBL and DDBJ databases under Accessions numbers DQ341586 to DQ341601. Our results have revealed that PvMSP5 is one of the P. vivax surface proteins having greater polymorphism, this being restricted to specific protein regions. The intron and exon II (which includes the GPI anchor and EGF-like domain) were both highly conserved when compared to exon I; exon I displayed the greatest variation and most of the recombination events occurred within it. No geographical grouping was observed. The Nei-Gojobori test revealed significant positive selection in the samples analysed here, whereas Tajima and Fu and Li tests presented a neutral selection pattern. The results reflected a localized variation pattern, recombination between PvMSP5 alleles and also functional and immune pressures, where stronger selective forces might be acting on exon I than on exon II, suggesting that the latter could be an important region to be included in an anti-malarial vaccine.